Hydrodynamic characteristics of the microbubble dissolution in water using an ejector-type bubble generator - I.G.N.B. Catrawedarma; Sefri Ton; Dadang Dwi Pranowo; Fredy Surahmanto (Case Studies in Chemical and Environmental Engineering)
This research uses an ejector bubble generator to determine water's flow structure and dissolved oxygen. The horizontal position of ejector, modified from conventional venturi, utilizes a gradual reduction in cross-section at the water inlet and contains air space before the mixing region. The bubble size distribution and the dissolved oxygen were measured experimentally, and empirical correlations were obtained from dimensional analysis, including the effect of Martinelli parameter. The characteristics of microbubble and volumetric mass transfer were investigated in the air flow range of 0.1–1.5 lpm and nozzle diameter of 1.17–3.50 mm. Bubble size distribution was obtained using image processing technique from a high-speed video camera, and dissolved oxygen was recorded using a polarographic dissolved oxygen meter. Based on the research variable, the air/water discharge ratio and nozzle diameter have a high impact on the bubble size with the power of 0.572 and 0.598 for bubble size correlation, respectively. They have power of −17.411 and 5.928 for oxygen transfer rate correlation, respectively. It shows that the air/water ratio and nozzle diameter significantly affect the bubble size and oxygen transfer rate.